Random amplified polymorphic DNA (RAPD) and enterobacterial repetitive intergenic consensus (ERIC) PCR of Vibrio cholerae from a foodborne outbreak in Limbang, Sarawak - Elexson, Nillian; Amirah, Z. J.; Joel, W.; Nick Laurence, Buyong; Dalene, Lesen; Tze, Y. T. (IFRJ, Faculty of Food Science & Technology, UPM., 2023)
Toxigenic and non-toxigenic V. cholerae strains can be monitored for changes in clones or serogroups, linkages between clinical and environmental isolates, genesis and clonal selection of epidemic strains, and population structure. Also, determining genetic relatedness among V. cholerae strains is critical for determining population genetic structure and evolutionary trends. In collaboration with the Sarawak Government Hospital, the present work was carried out on a total of 16 V. cholerae isolates in order to determine the genetic relatedness or heterogeneity of V. cholerae isolates from a foodborne outbreak among guests who attended a wedding ceremony in Limbang, Sarawak, Malaysia. The random amplified polymorphic DNA (RAPD) and enterobacterial repetitive intergenic consensus (ERIC) were conducted to compare and determine strains and trace diseasecausing microorganism. The RAPD fingerprinting was conducted using a total of 10-mer oligos 100 nmole random primers (OPAE1 - OPAE20). The primers OPAE7, OPAE10, OPAE14, and OPAE17 were selected because they were the most stable and discriminatory for V. cholerae. The PCR fingerprinting of ERIC-PCR was carried out using primer set of ERIC, ERIC1R (5’- ATGTAAGCTCCTGGGGATTCAC-3’), and ERIC2F (5’- AAGTAAGTGACTGGGGTGAGCG-3’). As a result, the 1 confirmed V. cholerae O1 samples were successfully fingerprinted. Based on the profiling results, the genetic fingerprint of some of the isolates from the clinical and environmental samples had 100% similarity, as indicated by the dendrogram. This indicated that the strains shared the same genetic profile. The smaller the genetic distance, the more homogeneous the strains are. The clinical and environmental strains shared some genetic characteristics. As indicated by the dendrogram, some strains were found to be closely linked to one another, while others were heterogeneous. Therefore, RAPD-PCR and ERIC-PCR produced the highest discrimination index. By combining these typing methods, evaluation of isolates' genetic diversity may be improved. The findings of the present work demonstrated the need for continued surveillance of V. cholera in Sarawak, Malaysia.